Computed tomography in patients with hypertrophic cardiomyopathy. Issue 2 (August 1984) - Stone, D L; Petch, M C; Verney, G I; Dixon, A K
Abstract : Computed tomography was undertaken in nine patients (age range 33-69 (mean 48.7) years) with hypertrophic cardiomyopathy. The ventricular septum was demonstrated in each patient and shown to be thickened (mean 25 mm at maximum width). The results agreed with those obtained by echocardiography, except in two patients in whom computed tomography showed preferential thickening of the mid-portion of the ventricular septum. The ventricular free wall was not clearly seen. Computed tomography may prove a valuable technique in the assessment of patients with hypertrophic cardiomyopathy.